Secrecy Performance of Decode-and-Forward Based Hybrid RF/VLC Relaying Systems - Jaber Al-Khori (16855470) (2019)
In this paper, we consider the secrecy of a hybrid radio frequency (RF)/visible light communication (VLC) system equipped with decode-and-forward relaying. We develop physical layer security algorithms that mitigate eavesdropping on both RF and VLC networks based on zero-forcing beamforming techniques. We evaluate the system performance in terms of secrecy capacity (SC) and outage probability (OP) for two network scenarios, namely non-cooperative (NCPS) and cooperative power saving (CPS) models. The NCPS case assumes fixed power at both source and relay while the CPS case assumes total average power shared between the source and relay. Our objective is to find the minimum power that satisfies a specific SC for both cases. Our simulation results show that CPS policy achieves higher SC and maintain lower OP compared with the NCPS one for the same amount of power. We also show that, for both cases, the hybrid RF/VLC network can improve SC compared with standalone RF or VLC networks. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2019.2891678